Cadernos de culinária familiar: espaço de recordação individual e coletiva - Sales, Alexandre Daher Ferreira (2021)
The present research considers the recipe books as object of memorialistic nature and family identity construction, because they carry, in their context, the application of knowledge that is transmitted from generation to generation, reverberating a sense of belonging. These objects are able to unveil a time dimension not exclusively chronological in the production of a dish, but the slow or fast time of mixing ingredients, which constitutes something proper and personal, family intimacy, affective, symbolic and aesthetic investments. In this sense, we aim to analyze familiar cooking notebooks as spaces of memory and of individual and collective writing of the twentieth century gastronomy, from a perspective of self-information evoked by the memory of the senses, also considering the affective memory, that is, the social memory in a kind of self-movement and of others. Regarding the specific objectives, we seek to identify the elements of individual and collective memory, from the inventory of cooking recipes that constitute the family recipe notebooks; analyze cooking recipes, extracting the aspects of everyday memory; highlight the aspects of the family relationship based on gastronomic practices; identify in the selected cookbooks, the relationship of food with social positioning and with the idea of differentiation to which it refers. The research is characterized as an exploratory-descriptive research outlined by a documentary study based on the corpus analysis of this research through the indiciary paradigm and documentary analysis, in addition to the personal and affective perceptions contained in the context of gastronomic information that constitute the cookbooks.